Prevalence of type 2 diabetes mellitus and other abnormalities of carbohydrate metabolism depending on diagnostic criteria - Alexander Vasil'evich Dreval' (Endocrinology Research Centre, 2010)
Aim. To assess current criteria for type 2 diabetes mellitus. Materials and methods. This screening study involving 2,368 residents of two municipal districts of the Moscow region was designed to elucidate differencesin the prevalence of abnormalities of carbohydrate metabolism depending on diagnostic criteria (WHO and ADA). Results. The prevalence of early disorders of carbohydrate metabolism and DM2 among the adult population of Moscow region is 17,1 and 7,2 respectivelyusing WHO criteria and 40,0 and 5,9% by ADA criteria. Conclusion. Refusal to undergo OGTT during screening decreases detectability of early metabolic disorders by 28,8 and 6,1% using WHO and ADAcriteria respectively. When screening is aimed to diagnose DM2 alone, OGTT can be omitted in subjects with fasting plasma glucose level below4,7 mmol/l. If it is aimed to diagnose both DM2 and impaired glucose tolerance, OGTT is not needed in subjects with fasting plasma glucose levelbelow 4,2 mmol/l. The use of ?combined? diagnostic criteria (i.e. OGTT according to ADA, but not WHO) significantly increases the prevalence ofmetabolic disorders from 24,9 to 48,8%.